Pyrolysis Process of Mixed Polypropylene (PP) and High-Density Polyethylene (HDPE) Waste with Natural Zeolite as Catalyst - Emi Erawati; Hamid Hamid; Annisa Ayu Ilma (Universitas Jenderal Soedirman, 2018)
The reactor of the experiment was made from stainless steel with the diameter of 25 cm and the height of 30 cm. The liquid petroleum gas was used as a fuel in the reactor. The reactor was connected by the thermocouple that controls temperature variations at 410, 420, 430, and 450ºC. Raw material contained plastic bottles and waste caps, while the natural zeolite as a catalyst was dried and cut in dimensions of 3x3 cm. A gas as the reacted product was condensed using the first condenser, then the liquid product was collected. Uncondensed gaswas condensed again in the second condenser, then the liquid product was collected again. The volume of gas was calculated based on the water volume coming out of the gallon. Thiswas repeated with varied ratios of plastics to natural zeolite (67:33; 75:25; 80:20; and 83:17 wt%). Pyrolysis was run for two hours and every 20 minutes the sample was weighed to gauge the change inmass of gas and liquid. After 120 minutes, the solid sample was examined to identify the mass of final solid. Based on the research, at the temperature of 440ºC, the highest liquid yield was 68.42%. On the other hand, with the ratio of raw material to zeolite at 83:17 wt%, the largest yield of liquid was 87.31%. The liquid product in various temperature and comparisons of percentage of raw material to catalyst was found to meet diesel specifications based on The Decree of Director General of Fuels and Gas Year 200,8 Number 14,496 K/14/DJM/2,008.